2020
DOI: 10.1007/978-3-030-62655-6_7
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality Surgical Training System for Office Hysteroscopy with Haptic Feedback: A Feasibility Study

Abstract: Hysteroscopy is a widely used gynaecological procedure to evaluate and treat cervical and intra-uterine pathology. In the last few decades, technical refinements in the optics technology, surgical accessories and the reduction of the outer diameter of the instrument have made it possible to perform many hysteroscopic procedures, including some operative procedures, in the office setting and without any anesthesia. Mini-hysteroscopic procedures in the office setting are associated with less pain, lower complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Execution time and trajectory length showed significant improvement, gradually decreasing in both mean and standard deviation for the novice and intermediate groups. These findings were somewhat expected, as previous studies in hysteroscopy training have also indicated positive change in these values [45] [46]. Another metric that showed great improvement over trials was the integral force.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Execution time and trajectory length showed significant improvement, gradually decreasing in both mean and standard deviation for the novice and intermediate groups. These findings were somewhat expected, as previous studies in hysteroscopy training have also indicated positive change in these values [45] [46]. Another metric that showed great improvement over trials was the integral force.…”
Section: Discussionsupporting
confidence: 80%
“…Since the authors were not able to find any representation of this metric in the literature, it is too early to draw a direct link between this metric and a trainee's level of skills. At the moment, we can only outline the observed decreasing trend in this value, both in the presented study and our previous work [46]. Additional research is required to investigate the validity of this metric.…”
Section: Discussionmentioning
confidence: 68%